2021
DOI: 10.7150/ijms.50883
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and prognostic factors of combined Hepatocellular Carcinoma and Cholangiocarcinoma, Hepatocellular Carcinoma and Intrahepatic Cholangiocarcinoma after Surgical Resection: A propensity score matching analysis

Abstract: Background: Clinical characteristics and prognosis among combined hepatocellular carcinoma (HCC) and cholangiocarcinoma (cHCC-CC) with HCC and intrahepatic cholangiocarcinoma (ICC) were inconsistent in previous studies. The aim of this study was to compare postoperative prognosis among cHCC-CC, HCC and ICC, and investigated the prognostic risk factor of cHCC-CC after surgical resection. Methods: A total of 1041 eligible patients with pathological diagnosis of cHCC-CC (n=135), HCC (n=698) and ICC (n=208) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Tumors with both unambiguously differentiated hepatocellular and biliary components are defined as cHCC-CCAs, based on the 2019 World Health Organization classification ( 1 ). The origin, biological behavior, treatment method and prognosis of cHCC-CCAs differ from HCCs and intrahepatic cholangiocarcinoma (ICCs), the first and second common primary hepatic malignancies ( 2 , 3 ). Liver resection may be the optimal treatment method for cHCC-CCAs, as pointed out by recent studies ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumors with both unambiguously differentiated hepatocellular and biliary components are defined as cHCC-CCAs, based on the 2019 World Health Organization classification ( 1 ). The origin, biological behavior, treatment method and prognosis of cHCC-CCAs differ from HCCs and intrahepatic cholangiocarcinoma (ICCs), the first and second common primary hepatic malignancies ( 2 , 3 ). Liver resection may be the optimal treatment method for cHCC-CCAs, as pointed out by recent studies ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of patients diagnosed with CHC almost doubled during 2004-2007 and 2012-2015, and patients with CHC more often had advanced T3-T4 stage cancer (57.0%) based on the guidelines of the American Joint Committee on Cancer (AJCC) and had a grim prognosis (2)(3)(4)(5). The prognosis of CHC was reported as comparable to that of ICC but was worse than that of HCC (6)(7)(8)(9)(10), and patients with CHC have a lower survival rate than those with both the aforementioned malignancies (11)(12)(13)(14). Therefore, the survival and prognosis of patients with CHC remain significant concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Cholangiocarcinoma (ICC) is an aggressive primary hepatic carcinoma originating in the bile duct epithelium [76]. Unlike HCC, surgical resection is currently the only treatment method for patients with ICC [77]. A study [78] extracted the most predictive radiomics features for evaluating MVI, perineural invasion, differentiation, Ki-67, VEGFR and CK7 in ICC and reported that these features had moderate efficiency in non-invasively predicting the biological behavior of ICC.…”
Section: Evaluation Of Tumor Biological Behaviors and Molecular Profilesmentioning
confidence: 99%